After Shelby County v. Holder, Can Independent Commissions Take the Place of Section 5 of the Voting Rights Act? - Brittany C. Armour (Washington University Journal of Law & Policy, 2017)
This Note traces the consequences of the Supreme Court’s decision in Shelby County v. Holder, which held unconstitutional the preclearance formula of the Voting Rights Act that required some states and counties to obtain federal authorization before changing voting procedures. Armour traces the history of the Voting Rights Act and the role independent commissions can play in ensuring that such facially neutral procedures do not have a disparate impact on minority communities. Armour advocates for independent commissions to take the place left empty by the Supreme Court’s rejection of the old preclearance formula suggesting that these commissions are a feasible way to effectively ensure citizens’ can vote without barriers.
Keywords: voting; voting laws; redistricting; discrimination; Shelby County v. Holder; Voting Rights Act; preclearnce; Arizona State Legislature v. Arizona Independent Redistricting Commission; Section 5; Section 4(b); independent commissions; civil rights